ANALYSIS OF BANK LIABILITY TO THE CRIME OF MONEY LAUNDERING BASED ON LAW NUMBER 8 OF 2010 - Uswah Hasanah (Proceeding International Seminar of Islamic Studies, 2022)
The types of crimes that destroy the foundations of the economic life of nations are increasingly flourishing. Money laundering is a new dimension of economic crime. Money laundering is a process carried out to change the results of criminal acts of corruption, narcotics, gambling, snuggling and other criminal acts by using banking services with the intention of hiding the origin of money. This study aims to further review the eradication of money laundering in Indonesia, which is regulated in Law Number 8 of 2010 concerning the Eradication and Prevention of Money Laundering. This research method is descriptive, using normative juridical legal research methods. The results of this study indicate that banks have a great responsibility in preventing and eradicating money laundering. For this reason, concrete steps are needed to identify, minimize and manage any risk originating from illicit money because it can threaten the viability of individual banking businesses and the financial industry as a whole. In this case, banks must have an effective audit mechanism and risk management mechanism and have sufficient resources to be able to comply with applicable regulations.Keywords: Money Laundering, Bank Accountability